2011
DOI: 10.1007/s13524-011-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Female Black-White Obesity Gap: A Decomposition Analysis of Proximal Causes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…US researchers have decomposed BMI across African–American and Caucasian males and females,37 38 concluding that unexplained differences between African–American and Caucasian were associated with one or a combination of potential factors including culture, genetics or unobserved (unmeasured) confounders. Other examples internationally have decomposed obesity between ethnic groups (eg, Chinese and Malays),39 between countries (eg, Italy and Spain),40 across sexes41 or over time42 and indicate that there can be large unexplained differences over the groups under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…US researchers have decomposed BMI across African–American and Caucasian males and females,37 38 concluding that unexplained differences between African–American and Caucasian were associated with one or a combination of potential factors including culture, genetics or unobserved (unmeasured) confounders. Other examples internationally have decomposed obesity between ethnic groups (eg, Chinese and Malays),39 between countries (eg, Italy and Spain),40 across sexes41 or over time42 and indicate that there can be large unexplained differences over the groups under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…211 Potential reasons for the greater burden of obesity in AA women include environmental, physiologic, and genetic influences. 1,1114 …”
Section: Introductionmentioning
confidence: 99%
“…energy intake) and exercise (e.g. energy expenditure) (33). Despite similar adherence to diet intake and exercise among black and white women enrolled in intervention trials, less weight loss has been reported among blacks (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing obesity prevalence to enhance cardiovascular health among blacks especially women, will require substantial public health efforts. These may include adapting culturally-tailored intensive lifestyle interventions (15, 33), implementing programs that improve ASCVD risk education, ensuring access to healthy foods and enhancing the built environment to promote physical activity.…”
Section: Discussionmentioning
confidence: 99%